An investigation of the flow rates of disposable bottle teats used to feed preterm and medically fragile infants in neonatal units across the UK in comparison with flow rates of commercially available bottle teats. (2nd October 2019) - Bell, Nicoll; Harding, Celia
ABSTRACT: Aims and Objectives: For preterm and medically fragile infants, learning to feed orally is challenging. There are many contributing factors that can support the development of oral feeding. The flow rate of a teat can influence feeding success in the bottle-fed infant and, if not supportive, can cause physiological instability during feeding. The flow rate of teats used in a selection of neonatal units in the United Kingdom (UK) was tested to determine their flow rate, which was then compared to the flow rate of commercially available teats. Design and Methods: Flow rate of teats used in several neonatal units across the UK were tested by attaching a teat to a breast pump and measuring the output of milk after 1 min. These values were compared to the flow rates of commercially available teats. The hypothesis was that hospital disposable teats might have a considerably higher flow rate, and a higher rate of variability, than commercially available teats. Results and Conclusions: The results identified that there were differing flow rates as well as a wide variation of flow rates for both hospital disposable and commercial teats. Hospital disposable teats had flow rates ranging from 8.5 mL/min to 23.3 mL/min, and commercial teats had a range of 4.2 mL/min to 31.3 mL/min. Measurement of variability in flow rate identified a moderate mean flow rate for hospital disposable teats (CoV = 0.1), with a low mean variability in flow rate for commercial teats (CoV = 0.07). Applicability of this data to a clinical context is discussed.